The Impact Of Montessori Based Learning On Early Childhood Cognitive And Social Development - Erwin Eka Saputra (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Montessori based learning has been widely applied in early childhood education as an approach that emphasizes independence, exploration, and social interaction. This study aims to analyze the impact of the Montessori method on the cognitive and social development of early childhood based on a literature review of various previous studies. The results of the study indicate that the Montessori approach has a positive influence on cognitive development, especially in the aspects of logical thinking, problem solving, and learning independence. In addition, in the social aspect, this method improves cooperation, communication, and emotional regulation skills in children. The implications of this study indicate that the application of the Montessori method in PAUD can be an effective strategy in improving children's holistic development.